2016
DOI: 10.1021/acschembio.5b00971
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Caspase-7 Specificity by Regio-Specific Mutations and Selection Provides Alternate Solutions for Substrate Recognition

Abstract: The ability to routinely engineer protease specificity can allow us to better understand and modulate their biology for expanded therapeutic and industrial applications. Here we report a new approach based on a caged green fluorescent protein (CA-GFP) reporter that allows for flow-cytometry-based selection in bacteria or other cell types enabling selection of intracellular protease specificity, regardless of the compositional complexity of the protease. Here we apply this approach to introduce the specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…Indeed, the engineering of the 'best' motif in a structurally well-exposed loop in a model protein resulted in a cleavage rate that still falls short of some known endogenous substrates, which has led to the proposal that other determinants, such as exosites, allow further improvement of catalysis [19]. In fact, usage of exosites by caspases has been demonstrated for cleavage of PARP-1 by caspase-7 [20], and there is evidence that cleavage of lamin A/C by caspase-6 also employs an exosite [21]. Taken together, features including adequate primary and secondary structures and the potential use of exosites allow tailoring (speed, completeness, timing) of substrate cleavage efficacy.…”
Section: What Is a Good Caspase Substrate?mentioning
confidence: 99%
“…Indeed, the engineering of the 'best' motif in a structurally well-exposed loop in a model protein resulted in a cleavage rate that still falls short of some known endogenous substrates, which has led to the proposal that other determinants, such as exosites, allow further improvement of catalysis [19]. In fact, usage of exosites by caspases has been demonstrated for cleavage of PARP-1 by caspase-7 [20], and there is evidence that cleavage of lamin A/C by caspase-6 also employs an exosite [21]. Taken together, features including adequate primary and secondary structures and the potential use of exosites allow tailoring (speed, completeness, timing) of substrate cleavage efficacy.…”
Section: What Is a Good Caspase Substrate?mentioning
confidence: 99%
“…Although the effector caspases are relatively closely related, caspases-3 and -7 are characterized as group II specificity, while caspase-6 shows group III specificity. The selection at P4 (D vs V) results in overlapping but nonidentical substrate profiles based on degradome analyses [27][28][29][30]. In the evolution of chordates, new caspase substrate specificities were important in developmental stages of the brain and nervous systems [31][32][33][34], so what may appear to be subtle changes in enzyme selection have large consequences in cellular development.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, substitutions from horizontal studies lack evolutionary context, where protein epistasis affects the specific combination of amino acids along discrete evolutionary paths [39,40]. Directed evolutionary approaches expand the sequence space that can be examined, and such studies identified a combination of amino acids that relax specificity in caspase-7, resulting in a shift in substrate cleavage profiles in cellulo of evolved-caspase-7 enzymes [30]. Evolutionary biochemical methods further expand the sequence space to include the entire protein, yet the methods simultaneously narrow the scope of the problem by also examining changes that occurred between common ancestral proteins [41].…”
Section: Introductionmentioning
confidence: 99%
“…Cleaved executioners can also experience a reversal to the zymogen-like state by small molecules (Hardy et al, 2004), which forces a loop rearrangement that traps L2’ over the dimer interface and results in the expulsion of loop 3 from the active site pocket. Following activation in the cell, each executioner caspase cleaves over a hundred substrates (Agard et al, 2012; Hill et al, 2016) to propagate the well-ordered termination of the dying cell.…”
Section: Introductionmentioning
confidence: 99%